The Development of Innovative Learning Resources with Project to Improve Student Critical Thinking Skill on The Teaching of Distillation - Grace Elisabeth Damanik; Manihar Situmorang (Ridwan Institute, 2022)
This research has a goal, namely to develop a project-based learning resource innovation in the form of Module in distillation subjects. in order to know its effectiveness to improve critical thinking skills and student learning outcomes. The model used in this research is ADDIE with three cycles in the implementation phase. The results of the development of project-based MFIs have an average according to BSNP standards = 85% with very feasible criteria and an N-gain score of 0.77, the proportion of 77.8% which states that project-based MFIs have high effectiveness. The field trial of the first cycle of the project design obtained the same value with M1 = 50; M2 = 89.37; M3 = 90.48; M4 = score 90.66 M4 > M3 > M2 >M1 which shows an increase in students' abilities in the refining learning process. the results of the pretest and posttest obtained the results of Mpostes = 46.25 and Mpostes = 88.23, so the test results show t count > t table which means H0 is rejected and Ha is accepted. project development results. based on the results of the calculation of the correlation between critical thinking skills and student learning outcomes obtained rxy count = 0.0066 with rxy table = 0.497 so that rxy count < rxy table then H0 is rejected and Ha is accepted with a positive correlation level with the conclusion that there is a relationship between critical thinking ability and student learning outcomes taught by the LKM developed on distillation material.